New Chances and New Responsibilities in the Arctic Region - Witschel, Georg (BWV Berliner Wissenschafts-Verlag, 2010)
Introduction by Rüdiger Wolfrum; Content; The Arctic: A Strategic Challenge for the 21st Century by Günter Gloser; Opportunities and Responsibilities in the Arctic Region: The European Union's Perspective by Joe Borg; The First Responsibility by Aqqaluk Lynge; An Explorer's Perspective by Arved Fuchs; New Chances and New Responsibilities in the Arctic Region: An Introduction by Georg Witschel; The Arctic in the Context of International Law by Rüdiger Wolfrum; Arctic in Change: New Prospects for Resource Exploitation and Maritime Traffic by Kirsten Ullbæk Selvig
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2009 -- Berlin; Internationales Recht; Umweltpolitik; Internationale Rohstoffpolitik; Arktis